Dalit, Labour And Stigma Against Waste Work: A Question Of Dignity And Self Respect. - Ankush Kumar (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
In the Indian context, some informal labour devoted to traditional occupation system, which based on the hierarchical caste structure, and as per the castes, occupations are divided. Lower caste principally the Dalit’s (ex-untouchable) traditional occupation relics considered worthless, dirty and filthy in a society and it further constructs stigma with their caste identity. Moreover, a peculiar kind of labour like a manual scavenger, ragpickers, and waste work consign one particular type of perception which produces deleterious vocabulary with damaging concepts like injustice, humiliation, indignity, and disrespect. The social phenomenon consisted of negative attribution of work with particular labour raises the questions: What kind of labour can produce dignity or is there any labour that consists of lower caste identity (Dalits) can generate dignity and respect or only the intellectual or so-called white-collar labour can produce dignity? This paper proposes one proposition and argument that the lower castes Dalits who are traditionally intricate in so-called polluted, dirty or filthy labour such as scavengers labour, leatherwork, and waste work, these forms of work dispense negative meaning and stigma with their labour. This theme and paper explore the questions mentioned above and try to comprehend the impression of labour, which spawns stigma with identity and dispense some negative provenance such as dirty, filthy, disgust, purity and pollution with caste identity.